Peran Guru dalam Membentuk Perilaku Anak Usia Dini di RA AL ISLAH - Salza Vyka Purnomo; Edo Dwi Cahyo (UIN Mataram, 2023)
The problem in this research is the teacher's role in shaping early childhood behavior at RA AL ISLAH. The purpose of this study was to find out how the teacher's role is in shaping the behavior of early childhood in RA AL ISLAH. The method used by researchers in this study is a descriptive method with a qualitative approach. The results of the analysis that researchers obtained at RA AL ISLAH are that there are four teacher roles that have been carried out by teachers at RA AL ISLAH such as being an educator in being polite, teaching in the process of socializing, trainers as well behaved teachers, and mentors directing students in learning seriously and focus in class. It is hoped that the four roles played by the teacher at RA AL ISLAH can help early childhood in forming good behavior within them.